Researching second language classrooms - McKay, Sandra (ESL & applied linguistics professional series)
Introduces teachers to research methods they can use to examine their own classrooms in order to become more effective teachers. The author emphasizes that what a teacher chooses to examine will dictate which method is most effective. Each chapter includes activities to help readers apply the methods described, often by analyzing research data.